THE ROLE OF SOCIAL MEDIA IN LEARNING ENGLISH (Spectrum Journal of Innovation, Reforms and Development, 2025)
The integration of social media into everyday life has led to significant changes in how people communicate, interact, and learn. This article explores the role of social media platforms in the process of learning English, examining how these platforms offer opportunities for language acquisition, communication practice, and cultural immersion. It also discusses the potential challenges and drawbacks, such as misinformation and the informal nature of online content, that learners may face when using social media for educational purposes.